Implementation of Pedagogical Competence of Islamic Religious Education Teachers at SMP Negeri 3 Surakarta - Santi Nurul Putri Meilina; Istanto Istanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to describe the pedagogical competence of Islamic Religious Education (PAI) teachers, identify the challenges they encountered, and analyze the strategies used to address these challenges among seventh-grade students at SMP Negeri 3 Surakarta. This study used a qualitative method, collecting data through observation, documentation, and interviews, and analyzing it inductively through data reduction, data display, and conclusion drawing. The results of the study showed that teachers had a high level of pedagogical competence, as reflected in their ability to plan learning activities, manage classrooms, understand student characteristics, and conduct continuous learning evaluation; however, several learning challenges were identified, including variations in students’ levels of understanding, low learning motivation, limited parental attention, and inadequate school facilities. The strategies implemented included providing remedial instruction for slower learners, offering enrichment materials for higher-achieving students, providing encouragement and motivation, collaborating with parents, and using available learning media. This study concluded that the pedagogical competence of Islamic Religious Education (PAI) teachers plays an important role in supporting effective learning; however, sustained improvements in learning outcomes require greater parental involvement and improved school facilities. Such pedagogical competence can be optimized to remain relevant and to positively affect Islamic Religious Education (PAI) teachers' efforts to support effective and efficient learning.